Network embeddedness, digital transformation, and enterprise performance—The moderating effect of top managerial cognition - Li, Yue; Fei, Guo Zhen (Frontiers in Psychology, 2023)
Under the new background of the explosive growth of digital economy and the deep integration of real economy, how to improve the performance level through digital transformation has become the key for enterprises to achieve high-quality development. Based on the embeddedness theory and the upper echelons theory, this paper studies the logic and mechanism of network embeddedness affecting enterprise performance, in order to describe the pre-motivations and complete influencing paths of digital transformation affecting enterprise performance, and promote enterprises to achieve high-quality development by means of digital transformation. Taking the middle and senior managers of 239 enterprises as the research objects, this paper applies hierarchical regression, bootstrap and other analysis methods for empirical test, and draws the following conclusions: (1) Relational embeddedness and cognitive embeddedness have a positive impact on digital transformation, while structural embeddedness has no significant impact on digital transformation. (2) Digital transformation has a significant positive impact on enterprise performance. (3) Digital transformation plays a significant mediating role between relational embeddedness, cognitive embeddedness and enterprise performance. (4) In the context of top managerial cognition, cognitive embeddedness can better improve enterprise performance through digital transformation. These results extend the previous literature on digital transformation, proves that digital transformation has a positive effect on enterprise performance. Meanwhile, top managerial cognition is conducive to shaping the dynamic capability of enterprises, and thus plays an important moderating role in the influence path of digital transformation on enterprise performance. This study further affirms the important role of top managerial cognition, which is conducive to enriching enterprises’ digital practices and improving enterprise performance.